The stress of the people of Kerinci Regency and Sungai Penuh City against the spread of COVID-19 - Dosi Juliawati; Hengki Yandri; Farid Imam Kholidin; Agung Tri Prasetia; Nur Rusliah; Aan Putra (Indonesian Journal of Counseling and Development, 2022)
Since the emergence of coronavirus disease (COVID-19) in Indonesia, Indonesian people have begun to show symptoms of anxiety and unrest in their days. It is also demonstrated by the community of Kerinci Regency and Sungai Penuh City so that the attitudes and behaviors indicated the signs of stress. This research aims to reveal the stress level of the people of Kerinci Regency and Sungai Penuh City against the spread of COVID-19. This research is early to uncover the stress data of the community by utilizing a descriptive quantitative study. The population of this research is the entire community of Kerinci Regency and Sungai Penuh City. They are willing to become respondents with a sample of 400 research people taken with convenience sampling techniques. Data is revealed using a scale of stress levels filled online and made anonymously; then, the research results are processed using the ideal score. This study showed that the average community of Kerinci Regency and Sungai Penuh City addressed the symptoms of stress analyzed from the emotional, physical, and behavioral responses. The results of this study suggest that counselors and psychologists take preventive measures to reduce the stress of the community by working with local governments.